2005
DOI: 10.1073/pnas.0408742102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoblastogenesis and bone mass by Wnt10b

Abstract: Wnts comprise a family of secreted signaling proteins that regulate diverse developmental processes. Activation of Wnt signaling by Wnt10b inhibits differentiation of preadipocytes and blocks adipose tissue development; however, the effect of Wnt10b on other mesenchymal lineages has not been defined. To explore the physiological role of Wnt signaling in bone development, we analyzed FABP4-Wnt10b mice, which express the Wnt10b transgene in marrow. Femurs from FABP4-Wnt10b mice have almost four times as much bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
666
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 790 publications
(719 citation statements)
references
References 42 publications
28
666
3
4
Order By: Relevance
“…Overexpression of Hoxd4 in the cartilage of transgenic mice has been found to reduce expression of Wnt3a, a canonical Wnt pathway ligand, suggesting a functional role for this homeobox transcription factor in multipotential stem cells capable of undergoing adipogenesis or chondrogenesis and a potential relationship to Wnt-related mechanisms (Kruger and Kappen 2010). This interpretation would be consistent with earlier studies determining that Wnt10b, another canonical Wnt pathway ligand, suppressed adipogenesis and promoted osteogenesis in multipotential stem cell models (Ross et al 2000;Bennett et al 2002Bennett et al , 2005.…”
Section: Discussionsupporting
confidence: 86%
“…Overexpression of Hoxd4 in the cartilage of transgenic mice has been found to reduce expression of Wnt3a, a canonical Wnt pathway ligand, suggesting a functional role for this homeobox transcription factor in multipotential stem cells capable of undergoing adipogenesis or chondrogenesis and a potential relationship to Wnt-related mechanisms (Kruger and Kappen 2010). This interpretation would be consistent with earlier studies determining that Wnt10b, another canonical Wnt pathway ligand, suppressed adipogenesis and promoted osteogenesis in multipotential stem cell models (Ross et al 2000;Bennett et al 2002Bennett et al , 2005.…”
Section: Discussionsupporting
confidence: 86%
“…A considerable body of data has now shown that differentiation of stem cells into adipocytes is also inhibited by signaling through certain Wnt pathways (40,41), which play an important role in stimulating new bone formation (42,43), supporting an inverse relationship between osteoblast and adipocyte differentiation (44). While this might appear contrary to our observations, it remains unclear if and at what stage in the evolution of an inflammatory lesion Wnt pathways might be important in SpA.…”
Section: Discussioncontrasting
confidence: 85%
“…WTX may be in a stochiometric relationship with other members of the b-catenin destruction complex and loss of its expression may hinder the complex, whereas overexpression does not lead to further assembly of such complexes. Nevertheless, as increased Wnt signaling is associated with increased skeletal ossification as seen in congenital WTX mutation, the available evidence does suggest that WTX is a negative regulator of canonical Wnt signaling (Bennett et al, 2005;Morvan et al, 2006;Jenkins et al, 2009). However, our results indicate that the ability of overexpressed WTX to slow cell growth and induce cell death is not associated with changes in b-catenin levels.…”
Section: Discussioncontrasting
confidence: 49%